Kontribusi supervisi akademik kepala sekolah, budaya sekolah dan kompetensi guru terhadap kinerja guru SMK Negeri 1 Saptosari - Warjono, Gandung; Najib, Khotim Hanifudin (Journal of Education Policy and Management Studies, 2024)
This study aims to determine the magnitude of contributions (1) academic supervision, school culture, teacher competence on the performance of teachers at the Saptosari Gunungkidul Vocational School (2) the school principal's academic supervision of teacher performance in Saptosari Gunungkidul Vocational School (3) school culture on teacher performance in Saptosari Gunungkidul District Vocational High School (4) teacher competency on teacher performance in Saptosari Gunungkidul State Vocational School. This research is a quantitative study, and is a research population where the population of the study is all teachers of the Saptosari Vocational High School which number 73 teachers. This study uses an ex-post facto approach, namely by testing what has happened to the research subjects. Data was collected through questionnaires using a Likert scale. Validate the contents of the expert judgment to examine the questionnaire instruments on material, language and measurement aspects. The construct validity of the instrument was tested using the product moment correlation technique from Carl Pearson. The reliability of the research instruments was tested by the Cronbach Alpha coefficient test. Data analysis was carried out after test requirements analysis, namely normality, linearity test, and multicollinearity test. The results of this study are as follows; 1) Academic supervision of principals, school culture, and teacher competencies on their own and together provide a positive contribution to the improvement of the performance of Saptosari State Vocational School teachers. This means that whenever there is an increase in the three variables, the performance of teachers in Saptosari District Vocational Schools will increase, 2) The results of the analysis show that teacher competencies make the greatest contribution to the work of Saptosari District Vocational School teachers, and academic supervision that provides the least contribution to the performance of state vocational school teachers as fast as Saptosari.